Analysis of Maintenance Planning and Scheduling of Plastic Packaging Production Machine Spout Products with RCM, RAM, and Preventive Maintenance Methods at PT. X - Daniel Chrisnanda; Etik Puspitasari (PT. Inovasi Teknologi Komputer, 2024)
PT. X is a plastic packaging manufacturing company, based on machine comparison in 2023, the spout assembly machine is the most critical machine because of the high frequency of downtime, which is 106 times. With the RCM method and RAM determination of critical components determined by FMEA, the RPN value at the very high-risk level (> 200) is; line feeder (681), gear (608), electric sensor (440) and pneumatic (224). Reliability value electrical sensor component 0.5 at (t) = 96 operating hours, transmission (t) = 108 operating hours, line feeder (t) = 120 operating hours, and pneumatic (t) = 729 operating hours. Maintainability of line feeder components maximally maintained for 3 hours = 81.1%, transmission 5.5 hours = 82%, electrical sensor 1.5 hours = 84.6%, pneumatic 2.5 hours = 83%. The results of maintainability value have been included in the IVARA standard (80%). Inherent Availability (AI) and Operational Availability (AO). AI of line feeder = 98%, transmission = 98%, electric sensor = 99%, and pneumatic = 99%. While the AO value of the line feeder component = 94%, transmission = 92%, electric sensor = 94%, and pneumatic = 85%. AI percentage reached IVARA level, but AO percentage did not reach IVARA level (95%). Maintenance schedule planning is: line feeder repair = 15 days, replacement = 8 weeks, gear; repair = 8 days, replacement = 9 weeks, electric sensor; repair = 178 days, replacement = 50 weeks, pneumatic; repair = 118 days, replacement = 33 weeks. Through the predetermined maintenance cost savings for the company with the comparison results, the estimated savings is Rp83,881,208 or 51.9%